2013
DOI: 10.1021/ac3034757
|View full text |Cite
|
Sign up to set email alerts
|

Relative Quantitation of Glycoisoforms of Intact Apolipoprotein C3 in Human Plasma by Liquid Chromatography–High-Resolution Mass Spectrometry

Abstract: Glycosylation is one of the most important post-translational modifications to mammalian proteins. Distribution of different glycoisoforms of certain proteins may reflect disease conditions and, therefore, can potentially be utilized as biomarkers. Apolipoprotein C3 (ApoC3) is one of the many plasma glycoproteins extensively studied for association with disease states. ApoC3 exists in three main glycoisoforms, including ApoC3-1 and ApoC3-2, which contain an O-linked carbohydrate moiety consisting of three and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…This is then linked to reduced inhibition of lipoprotein lipase and improved triglyceride clearance. In line, the production rate of apoC-III 1 and -III 2 is more strongly correlated with plasma triglyceride levels than apoC-III 0 (Mauger et al 2006), increased apoC-III 1 / apoC-III 0 ratio has been found in diabetic subjects (Jian et al 2013), and HDL3 from subjects with low HDL-C is characterised by higher levels of monosialylated apoC-III than subjects with high HDL-C (Mazur et al 2010). The evaluation of apoC-III isoforms is complicated by the fact that apoC-III 0 can be separated into a non-glycosylated form and glycosylated but non-sialylated forms (Bruneel et al 2008;Holleboom et al 2011;Nicolardi et al 2013a).…”
Section: Protein Isoforms Translational and Posttranslationalmentioning
confidence: 57%
“…This is then linked to reduced inhibition of lipoprotein lipase and improved triglyceride clearance. In line, the production rate of apoC-III 1 and -III 2 is more strongly correlated with plasma triglyceride levels than apoC-III 0 (Mauger et al 2006), increased apoC-III 1 / apoC-III 0 ratio has been found in diabetic subjects (Jian et al 2013), and HDL3 from subjects with low HDL-C is characterised by higher levels of monosialylated apoC-III than subjects with high HDL-C (Mazur et al 2010). The evaluation of apoC-III isoforms is complicated by the fact that apoC-III 0 can be separated into a non-glycosylated form and glycosylated but non-sialylated forms (Bruneel et al 2008;Holleboom et al 2011;Nicolardi et al 2013a).…”
Section: Protein Isoforms Translational and Posttranslationalmentioning
confidence: 57%
“…Solid phase extraction (SPE) is another purification technique that is employed solely or along with other purification techniques for sample clean up wherein the analyte is a smaller protein or peptide [12,[14][15][16][17]. Several mixed mode SPE cartridges, combining reversed phase stationary phase along with strong cation exchange or weak anion exchange, are commercially available for peptide analysis.…”
Section: Non-selective Protein Enrichment Techniquesmentioning
confidence: 99%
“…Columns with larger pore stationary phases (300 Å) allow improved penetration of larger molecules as well as the use of higher flow rates with reduced band broadening, and therefore provide greater selectivity for some peptides and proteins. Two-dimensional chromatographic separations, such as ion-exchange chromatography (IEC)-RPLC or RPLC-HILIC, have been utilized to fractionate and clean up samples, thus improving sensitivity of detection [16,24,46,52,53]. Additionally, many reported methods have used column trapping prior to analytical separation.…”
Section: Chromatographic Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, several proteoforms of apoCs exist [32] which reflect their function in vivo . MS-based methods provide a unique opportunity to study apoCs proteoforms [3337], and correlate their structural modifications with function in physiological and pathological states.…”
Section: Introductionmentioning
confidence: 99%